TINGGALAN WARISAN BUDAYA DI KOTA PANGKALPINANG SEBAGAI SARANA EDUKASI SEJARAH LOKAL MASYARAKAT - Kahfi, Mishbah Fial; Prasodjo, Tjahjono (Jambura History and Culture Journal, 2024)
The diversity of cultural heritage remains in Pangkalpinang City contains various important information related to identity of the community. These cultural heritages intersect with each other and have historical values that can be a source of local history learning for the people in Pangkalpinang City. The approach to this research use historical education for the community. These local history learning resources can be provided formally through education in schools or non-formally through outreach to the community by utilizing existing Cultural Heritage or the Indonesian Tin Museum.